Improvement of color quality and reduction of defects in the ink jet-printing technology for ceramic tiles production: A Design of Experiments study. Issue 1 (January 2016) - Montorsi, Monia; Mugoni, Consuelo; Passalacqua, Alessio; Annovi, Andrea; Marani, Fabrizio; Fossa, Ludovica; Capitani, Raffaele; Manfredini, Tiziano
Abstract: The aim of the present work was to study the effect of different process parameters on the color and defects of tiles produced by ink-jet printing technology. The Design of Experiment approach was used to guarantee a rational planning of the experiments and to ensure objective conclusions through the statistical analysis of the data. Particularly, correlations between the process parameters and the quality of decorated tiles in terms of color and presence of surface defects were extensively investigated. Microstructural analysis was used to explain the results derived by the statistical analysis of the data obtained by the rational plan of the experiments allowing further insight in the structural features and mechanisms correlated to the macroscopic properties of the tiles. The study supplied an efficient way to control the final quality of the decorated tiles satisfying the quality standards required by the market demand.